Land reform in Moldova: how viable are emerging peasant farms? An assessment referring to a recent World Bank study - Martin Petrick (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2000)
Based on a case study of two Moldovan regions, the paper challenges the favourable assessment of recently established peasant farms in a World Bank study by LERMAN et al. (1998). The main arguments in favour of a more critical view of the results of land privatisation and farm restructuring are that a) private farmers produce only on a minimal fraction of land with almost no machinery or purchased inputs at all, b) the income of a typical farm household is below a poverty line based on national standards, c) private farmers face substantial production and marketing risks, d) at present, it is unlikely that short- or long-term investment projects in agriculture can be credit funded. Currently, peasant farms are mainly run to produce a minimum diet for the affiliated household. The situation thus gives little reason for rosy future perspectives concerning a market-oriented, commercial private agriculture. – – Der vorliegende Beitrag setzt sich mit der positiven Bewertung neugegründeter Kleinbauernwirtschaften durch eine kürzlich veröffentliche Weltbank-Studie von LERMAN et al. (1998) auseinander. Er beruht auf Ergebnissen einer Fallstudie von zwei Moldauischen Regionen. Folgende Argumente sprechen für eine wesentlich kritischere Bewertung der Ergebnisse des Privatisierungs- und Umstrukturierungsprozesses: a) Private Kleinbauern produzieren lediglich auf einer minimalen Landfläche mit praktisch keinen Maschinen oder zugekauften Betriebsmitteln; b) das Einkommen eines typischen kleinbäuerlichen Haushalts liegt unterhalb einer Armutsgrenze, die auf nationalen Standards beruht; c) Private Kleinbauern sehen sich bedeutenden Produktions- und Vermarktungsrisiken gegenüber; d) die Wahrscheinlichkeit, dass kurz-oder langfristige Investitionen in der Landwirtschaft durch Kredite finanziert werden können, ist gegenwärtig gering. Zur Zeit werden private Bauernwirtschaften hauptsächlich zur Sicherung einer ausreichenden Nahrungsmittelversorgung der zugehörigen Haushalte betrieben. Die Situation gibt daher wenig Grund für Zukunftsaussichten, die eine marktorientierte, kommerziell betriebene private Landwirtschaft erwarten.
urn:nbn:de:gbv:3:2-22939
Keywords: Q12; Q15; P36; 330; Agriculture in transition; Land reform; Poverty; Subsistence farming; Moldova; Landwirtschaft im Transformationsprozess; Landreform; Armut; Subsistenz; Moldau; Agrarreform; Bodenreform; Landwirtschaftlicher Kleinbetrieb; Privatisierung; Unternehmensgründung; Ländliche Armut; Subsistenzwirtschaft; Landwirtschaftliche Entwicklung; Moldawien